Varying patterns of risk factors for inflammatory bowel disease in the East and the West: insights from the global burden of disease study 2021 - Yiming Zhang; Li Wang; Hong Yang (BMC Public Health)
Abstract Background Certain risk factors for inflammatory bowel disease (IBD) have not been thoroughly examined. The disparity in IBD risk factors between Eastern and Western regions remains inadequately understood. This study seeks to comprehensively investigate global IBD risk factors and delineate the differences between Eastern and Western populations. Methods The global epidemiological data were gathered by extracting data from a prior systematic review and adding the data from the studies conducted between 1980 and 2021 through a systematic search of the PubMed database from 1 January 2017 to 31 August 2023. Risk factor data were obtained from the Global Burden of Diseases, Injuries, and Risk Factors Study (GBD) 2021. These datasets were utilized to analyze IBD risk factors and compare regional differences between the East and West. Results Our primary finding indicates that some environmental, nutritional, and occupational risks are predominantly higher in the East, whereas dietary risks are more pronounced in the West. Furthermore, the relationship between risk factors and incidence trends varies between these regions. Notably, previously underrecognized risk factors, such as occupational hazards and child maltreatment, were found to be associated with IBD. Moreover, lower systolic blood pressure and decreased exposure to ambient ozone pollution were linked to a declining trend in Crohn’s disease incidence. Higher bone mineral density and a reduced risk of childhood underweight were correlated with a declining trend in ulcerative colitis incidence. Conclusions The risk factors for IBD exhibit varying patterns between Eastern and Western populations. Furthermore, these risk factors may exert differential effects on IBD patients across these regions.